THE INFLUENCE OF DIETARY SALVIA AND LAVENDER POWDERS ON PRODUCTIVE PERFORMANCE, SOME PHYSIOLOGICAL PARAMETERS, AND IMMUNITY OF BROILER UNDER STOCKING DENSITY STRESS - Mustafa, Alaa Ab.; Tayeb, Ihsan T. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2022)
The purpose of this experiment was to increase poultry meat production by increasing the number of chickens reared in the same area and managing it by using medicinal herbs Salvia officinalis L and Lavandula angustifolia L. in the broiler chicken diet. 705 one-day-old chicks were randomly distributed into to7 treatments with three replicates for an area of two m2 floor system in each replicate for each treatment, during 35 days of the study. T0 negative control 75 chicks, 25 chicks for each replicate 12-13 chicks per m2 fed standard diet. T1 positive control (stocking density without supplementation)105 chicks, 35 each replicate chicks 17-18 per m2 fed standard diet. The same stocking density for T2, T3, T4, T5, and T6 have been given standard feed with supplemented herbals, salvia 0.7%, 0.9%, lavender0.7%, 0.9%, and mixed 0.7% respectively. Depending on the results, chickens reared in stress stocking density with supplementations led to higher improvement of body weight, meat production, body weight gain (BWG), feed conversion ratio(FCR g feed/g weight), production index PI, carcass weight (g) and dressing percentage, RBCs 106cells/mm3, lymphocyte%, of increasing activity of thyroid hormones T3, T4 (nmol/L) boost antibody titers of ND and IBV when compared with positive control. However, heterophil%, stress indicator H/L ratio, glucose mg/ dL and cholesterol mg/ dL significantly reduced. The results showed that adding sage and lavender plants to broiler feed is effective in improving productivity, immunity, and resistance characteristics in reducing the adverse effects of stress caused by increasing the intensity of broiler rearing in the same area.